Exploring EFL Students' Willingness to Communicate: The Role of Motivation in English Learning - Sri Purwaningsih; Alamsyah Harahap (EduInovasi: Journal of Basic Educational Studies, 2025)
This research emphasizes the need for more attention in improving students' confidence in communicating with English as well as exploring other factors that affect students' learning motivation. The purpose of the research is to explore the factors influencing EFL (English as a Foreign Language) students' willingness to communicate (WTC) and their motivation in English communication. The study aims to identify how intrinsic and extrinsic motivations affect students' confidence and participation in speaking activities, ultimately allowing educators to tailor teaching strategies to better meet students' needs. The principal results indicate that students' assessment of their English-speaking ability falls into two main categories based on their scores: those scoring 0-5 (69.23%), who exhibit lower confidence and are hesitant to participate due to fear of mistakes and social anxiety, and those scoring 6-10 (30,76%), who demonstrate higher confidence and are more engaged in class discussions and presentations. This suggests a significant correlation between motivation levels and students' willingness to communicate. The major conclusions drawn from the research highlight the importance of fostering both intrinsic and extrinsic motivation to enhance students' WTC. By creating a supportive learning environment and employing engaging teaching methods, educators can help students overcome their fears and anxieties, thereby improving their communication skills in English. Speaking is one of necessary skill to communicate, so the researcher asserts the things needed to enhance students’ confidence to communicate in English and also to find out the exclude factors which can influence their learning motivation. This research aimed to find out the Factors influencing EFL (English Foreign Language) Students’ Willingness to communicate (WTC) and their motivation in Speaking to do a communication. It explored how intrinsic and extrinsic motivation affect students to be confidence and take a part in the speaking activities. Those actually to help teacher ready with the analysis of the students’ need before delivering the material in EFL class. The finding showed that There are two main categories of students in the English-speaking ability from the assessment given. The first one is scoring 0-5 (69,23%)